Characteristics of Triassic epithermal Au mineralization at the Q prospect, Chatree mining area, Central Thailand. Issue 2 (April 2014) - Tangwattananukul, Ladda; Ishiyama, Daizo; Matsubaya, Osamu; Mizuta, Toshio; Charusiri, Punya; Sato, Hinako; Sera, Koichiro
Abstract: The Chatree deposit is located in the Loei‐Phetchabun‐Nakhon Nayok volcanic belt that extends from Laos in the north through central and eastern Thailand into Cambodia. Gold‐bearing quartz veins at the Q prospect of the Chatree deposit are hosted within polymictic andesitic breccia and volcanic sedimentary breccia. The orebodies of the Chatree deposit consist of veins, veinlets and stockwork. Gold‐bearing quartz veins are composed mainly of quartz, calcite and illite with small amounts of adularia, chlorite and sulfide minerals. The gold‐bearing quartz veins were divided into five stages based on the cross‐cutting relationship and mineral assemblage. Intense gold mineralization occurred in Stages I and IV. The mineral assemblage of Stages I and IV is characterized by quartz–calcite–illite–laumontite–adularia–chlorite–sulfide minerals and electrum. Quartz textures of Stages I and IV are also characterized by microcrystalline and flamboyant textures, respectively. Coexistence of laumontite, illite and chlorite in the gold‐bearing quartz vein of Stage IV suggests that the gold‐bearing quartz veins were formed at approximately 200°C. The flamboyant and brecciated textures of the gold‐bearing quartz vein of Stage IV suggest that gold precipitated with silica minerals from a hydrothermal solution that was supersaturated by boiling. The δ 18 O values of quartz in Stages I to V range from +10.4 to +11.6‰ except for the δ 18 O value of quartz in Stage IV (+15.0‰). The increase in δ 18 O values of quartz at Stage IV is explained by boiling. PH2O is estimated to be 16 bars at 200°C. The fCO2 value is estimated to be 1 bar based on the presence of calcite in the mineral assemblage of Stage IV. The total pressure of the hydrothermal solution is approximately 20 bars at 200°C, suggesting that the gold‐bearing quartz veins of the Q prospect formed about 200 m below the paleosurface. Abstract : Coexistence of laumontite, illite and chlorite in the gold‐bearing quartz vein of Stage IV suggests that the gold‐bearing quartz veins were formed at approximately 200°C. Quartz showing flamboyant texture in Stage IV suggests rapid crystal growth. The total pressure of the hydrothermal solution is approximately 20 bars at 200°C, suggesting that the gold‐bearing quartz veins of the Q prospect formed about 200 m below the paleosurface.